The role of nutrients in severe acute respiratory syndrome coronavirus 2 infection - Sengupta, Aditi Munmun; Chatterjee, Diptendu; Ghosh, Rima; Nakhro, Khriesivonuo; Chakravarti, Ipsita; Bhattacharya, Salil Kumar (Asian Journal of Medical Sciences, 2022)
Balanced and healthy nutrition is a vital to attain a good immune response. Numerous studies have reported that boosting up adaptive immunity through nutritional interventions can impede viral infections. With the present leading challenge of the COVID-19 pandemic globally, maintaining good nourishment is indispensable to remain immune against the novel virus. By and large, ineffectively fed people are at a higher risk of creating different kinds of contaminations. In addition, constant and extreme contagion can cause health problems and demolish a patient’s nourishing status, making them susceptible to different diseases. During the COVID-19 pandemic, everyone must screen their eating routine and nourishing status. Good nutrition can subside the ongoing unprecedented health complications and deaths. Evaluating the clinical status of COVID-19 cases at the hour of clinic confirmation is strongly recommended. Specific dietary help is prescribed to be given to those in the high-hazard bunch, asymptomatic transporters, and patients with moderate or extreme COVID infection. An assortment of micronutrients techniques to treat COVID-19 can prove beneficial at the preliminary stage of the clinical attendance. The prompt supplementation of specific supplements in gentle cases can forestall the movement of sicknesses.